Characterizing a highly excited and sustained brain response activity during gaming: P300-CE - Leisi Pei; C. Shawn Green; Guang Ouyang (Proceedings of the National Academy of Sciences, 2025)
Inspired by the high engagement and sustained behavioral excitement observed in video game players, we hypothesized that distinct brain activity patterns occur during gaming compared to a generic nongame setting. Using electroencephalography (EEG), we characterized the brain’s response to critical in-game events, focusing on the response magnitude and adaptation. Data from a large participant cohort (n = 140 for game tasks, n = 200 for nongame tasks) revealed a clear, definite, and consistent temporospatial structure of brain response patterns triggered by critical in-game events. Most notably, this response displayed unusually large magnitudes and a lack of adaptation over repeated exposures—markedly different from the observed neural responses to typical events in lab-based tasks (e.g., regarding novelty, unexpected events or errors). The identification of this distinctive response component in gaming contexts may inspire further research into fundamental cognitive systems, such as motivation, reward, emotional engagement, and their dynamic interplay in gaming environments.